1992
DOI: 10.1007/bf02536480
|View full text |Cite
|
Sign up to set email alerts
|

α‐Helical requirements for free apolipoproteins to generate HDL and to induce cellular lipid efflux

Abstract: The structural requirement has been studied for apolipoproteins in their free form to interact with cells, to generate high density lipoprotein (HDL), and to cause cellular lipid efflux (J. Biol. Chem. 266, 3080-3086, 1991). It is shown that human apolipoprotein (apo) A-IV and apolipophorin III of Manduca sexta cause cholesterol efflux from cholesterol-loaded mouse peritoneal macrophages and reduce intracellularly accumulated cholesteryl ester as a result of forming HDL-like particles with cellular lipids, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…These results strongly suggest that le represents the mean Of duplicate dishes (3.5%/ coefficient )n). surface, as has been described previously for the interaction of sure of fibroblasts to apo A-I or 37pA increased efflux HDL apolipoproteins with cells (28,32). This property may plasma membrane of both cholesterol and phosphaticonfer specificity for lipid-poor subclasses of HDL particles ie in parallel to depletion of ACAT-accessible choleswhich have more helices exposed for cellular interactions (7, plying that these three lipid transport processes are 33,34 Previous studies showed that modifying HDL so as to decrease its interaction with cellular high-affinity binding sites also reduces its ability to remove excess cellular cholesterol (4,5,(35)(36)(37), suggesting that these two processes are closely I .…”
Section: Discussionsupporting
confidence: 53%
“…These results strongly suggest that le represents the mean Of duplicate dishes (3.5%/ coefficient )n). surface, as has been described previously for the interaction of sure of fibroblasts to apo A-I or 37pA increased efflux HDL apolipoproteins with cells (28,32). This property may plasma membrane of both cholesterol and phosphaticonfer specificity for lipid-poor subclasses of HDL particles ie in parallel to depletion of ACAT-accessible choleswhich have more helices exposed for cellular interactions (7, plying that these three lipid transport processes are 33,34 Previous studies showed that modifying HDL so as to decrease its interaction with cellular high-affinity binding sites also reduces its ability to remove excess cellular cholesterol (4,5,(35)(36)(37), suggesting that these two processes are closely I .…”
Section: Discussionsupporting
confidence: 53%
“…HDL is generated by the ABCA1-mediated reaction with various peptides having amphiphilic a-helical segments, including helical apolipoproteins (35,45), synthetic peptides (46,47), and even those containing only D-amino acids (44,48). Thus, there is no specific requirement of amino acid sequence for the biogenesis of HDL except for amphiphilic helices as a key conformation.…”
Section: Discussionmentioning
confidence: 99%
“…The generally accepted model for efflux mediated by these two proteins is that the ligands for SR-BI-mediated efflux are mature, fully lipidated lipoproteins rich in PL (10,27). In contrast to SR-BI, the ligands for ABCA1-mediated efflux appear to be poorly lipidated, exchangeable apolipoproteins such as apoA-I, apoA-II, apoA-IV, and apoE (28)(29)(30)(31). This model of cellular cholesterol efflux is derived primarily from studies with cultured cells exposed to purified preparations of lipoproteins or apolipoproteins.…”
Section: Discussionmentioning
confidence: 99%